El nombre de los hoteles espa\~noles : un análisis del naming de los hoteles en Benidorm y Alicante - Fernando Olivares-Delgado; Daniel Rodríguez-Valero; Alberto Pinillos-Laffón; María Teresa Benlloch-Osuna (Revista de marketing y publicidad, 2024)
The importance of branding in tourism and hospitality has been the subject of study by the scientific community. However, there is little specific work on brand names in this sector. It is necessary to delve deeper into the predominant naming criteria in the names of hotels and other types of tourist accommodations. We have analyzed the hotel company name in a sample of 212 tourist accommodations, mostly SMEs and family businesses. The results indicate that, regarding the chosen naming criteria, there is mainly a difference between the criteria chosen to name hotels and those chosen to name other types of tourist accommodations, with the latter being more descriptive and less suggestive or evocative. The most recurring naming criterion in the sector is “fantasy” or “creative”. This research aims to expand knowledge about the choice of corporate name in the hospitality sector, based on the typology established by the scientific community, so that it can serve as a reference point for future research on naming or branding.
10.51302/marketing.2024.21373; 10.51302/marketing.2024.21373; 3122839-2; 2792-405X; Revista de marketing y publicidad; 1807916111